THE CONCEPT OF "SCIENCE FICTION" IN LITERATURE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Through imaginatively created narratives according to the scientific foundations given in our article, this allows us to study futuristic scenarios, study the moral consequences of scientific achievements and think about the secrets of the universe. By combining elements of Science, Technology and philosophy, science fiction goes beyond pure entertainment, giving us a means to think about our current world and think about the path ahead. In literature, the concept of science fiction is a rich and dynamic genre that invites readers to explore the possibilities of human existence.